IMPLEMENTASI KEBIJAKAN LINGKUNGAN UNI EROPA DALAM COP21 - Adam Bima Laputro, (2021)
This research raises the issue of climate change as a serious problem that threatens human existence and explains the efforts of international actors and institutions of international roles in dealing with the issue. The author makes the United Nations Convention on Climate Change and the European Union the institutions that are the main focus of research in overcoming and regulating climate change issues. This research is a qualitative research and uses the approach of climate change theory and institutionalism as a research reference. The authors find that the implementation of the European Union's environmental policies supports the Paris Agreement targets.